Amelia Bedelia road trip! - Parish, Herman; Avril, Lynne, 1951- (New York, NY : Greenwillow Books, an imprint of HarperCollins Publishers, 2013)
Fun and fiascoes ensue when young Amelia Bedelia and her parents take a road trip through their state.
3.1
K-3.
K-3
Keywords: Amelia-Bedelia -- (Fictitious character) -- Juvenile fiction; Amelia-Bedelia -- (Fictitious character) -- Fiction; Amelia-Bedelia -- (Fictitious character) -- Fiction; Automobile travel -- Juvenile fiction; Families -- Juvenile fiction; Vacations -- Juvenile fiction; Automobile travel -- Fiction; Family life -- Fiction; Humorous stories; Vacations -- Fiction; Automobile travel -- Fiction; Family life -- Fiction; Vacations -- Fiction; Humorous fiction